Energy efficiency in Brazilian industrial plants: knowledge management and applications through an expert system - Buccieri, Gilberto Paschoal [UNESP]; Balestieri, José Antonio Perrella [UNESP]; Matelli, José Alexandre [UNESP] (Springer Nature, 2020)
This article presents the application of an expert system (ES) prototype as an intelligent tool for preliminary diagnostics of energy efficiency (EE) potential in Brazilian industrial plants and knowledge management (KM) in organizational environments, aimed especially to small- and medium-sized enterprises. The prototype provides the diagnostics rationale through a module for an explanation to support the decision making and provide insights regarding the adoption of EE actions. The knowledge base required by the prototype is built from the expertise and experience of a group of experts in EE and professionals from the industrial sector. The knowledge acquired from this interaction is represented in the form of rules, which are computationally implemented through a well-known tool for developing ES. Then, the resulting prototype is validated by the same group of multidisciplinary experts. Two different applications are presented to demonstrate the possibilities of EE improvement in industrial plants. These applications also show the ES as a valuable resource for organizational KM. In such a context, the ES creates a permanent corporate memory regarding EE, so that the access to this knowledge is independent on the availability of the human experts in the area. The ES also turns EE expertise into lasting value through sharing and retention actions, contributing to further improvements and processes continuity.
Keywords: Energy efficiency; Expert systems; Industry; Knowledge management; Small- and medium-sized enterprises (SME)